The renal angina index accurately predicts low risk of developing severe acute kidney injury among children admitted to a low-resource pediatric intensive care unit - Christina Zulu; Chisambo Mwaba; Somwe wa Somwe (Renal Failure, 2023)
Background Acute kidney injury (AKI) increases the risk of adverse outcomes. The renal angina index (RAI) has previously been used to predict patients at risk of developing severe AKI (sAKI).Method This single-centre prospective observational study aimed to assess the prevalence of sAKI in PICU as the primary outcome and the duration of mechanical ventilation and PICU stay, RRT need, and mortality as secondary outcomes. The utility of the RAI in predicting day 3 sAKI was also assessed. We enrolled 122 patients aged 1 month to 16 years whose baseline characteristics were collected via questionnaire. RAI was calculated on day 0 with a score of ≥8 being considered positive. sAKI was defined as KDIGO stages 2 and 3.Results sAKI prevalence was 14.8% and its development was associated with longer duration of mechanical ventilation (p = 0.001) and higher mortality (p = 0.011). A positive Day 0 RAI predicted day 3 sAKI with sensitivity 55.6%, specificity 85.6%, PPV 40.0%, NPV 91.8%, and AUC of 0.77. Exclusion of children older than 5 years improved RAI performance (sensitivity 72.7%, specificity 88.0%, PPV 57.1%, NPV 93.6%, AUC 0.80). A modified RAI based on local AKI risk factors had equivalent performance to RAI (Z – score 0.78 (CI −0.077–0.033), p = 0.435) with sensitivity 72.2%, specificity 80.8%, PPV 39.4%, NPV 94.4% and AUC 0.80.Conclusion The RAI can be an effective tool in ruling out sAKI in patients and a modification of RAI based on population-based risk factors improves the test’s sensitivity and NPV.